Celecoxib is a CYP1A2 inhibitor in vitro but not in vivo - Karjalainen, Marjo J.; Neuvonen, Pertti J.; Backman, Janne T. (European journal of clinical pharmacology, 2008)
Background and objective We recently discovered that rofecoxib is a potent mechanism-based inhibitor of CYP1A2. The effect of the widely used cyclo-oxygenase-2 selective non-steroidal anti-inflammatory drug celecoxib on CYP1A2 activity has not been reported. Methods The effect of celecoxib on CYP1A2 activity (phenacetin O-deethylation) was first studied in vitro using human liver microsomes. This was followed by a randomized, placebo-controlled, cross-over study in which 12 healthy volunteers were given celecoxib (200 mg twice daily) or placebo for 4 days. On day 3, a caffeine test was performed. On day 4, the subjects ingested 2 mg tizanidine. Plasma samples for the measurement of the concentrations of tizanidine, its metabolites and celecoxib were collected up to 24 h post-administration. Pharmacodynamic variables (e.g. blood pressure, subjective drowsiness and drug effect) were recorded up to 12 h post-adm. Results Celecoxib was found to be a moderately potent competitive inhibitor of CYP1A2 in vitro with a K i (inhibitor constant) of 25.4 μ M . However, in vivo, celecoxib did not affect the caffeine test, or the peak concentration, time to peak concentration, area under the concentration-time curve or half-life of tizanidine. The pharmacodynamic variables of tizanidine also remained unchanged. Conclusions Unlike rofecoxib, celecoxib does not clinically to significantly inhibit CYP1A2. The lack of significant in vivo inhibition of CYP1A2 can be correctly predicted on the basis of in vitro K i data and the free peripheral or portal plasma concentration of celecoxib.